Ketersediaan Sumber Belajar Bahasa Indonesia di SMP Negeri 2 Gondangrejo - Anita Zanjabila; Laili Etika Rahmawati (Jayapangus Press, 2022)
This study aims to determine the availability of Indonesian language learning resources at SMP Negeri 2 Gondangrejo. This research is a qualitative descriptive study with a qualitative approach. The research was conducted through interviews with Indonesian teachers in grades 7, 8, and 9. The research location was SMP Negeri 2 Gondangrejpo. There are two kinds of Indonesian language learning resources available at SMP Negeri 2 Gondangrejo, namely books and the internet. Indonesian language learning resources sourced from books are books from the government in 2018. The availability of Indonesian language learning resources at SMP Negeri 2 Gondangrejo in addition to books, namely the internet. Karanganyar Regency created a website called Indoprima, this website is used for grades 7, 8, and 9. Indonesian language teachers for grade 7 have a learning innovation during this pandemic by creating a radio web. This web radio is called Esperojo.fm. The results of this study are the availability of Indonesian language learning resources at SMP Negeri 2 Gondangrejo already using learning resources well. So that from the source of learning Indonesian at SMP Negeri 2 Gondangrejo achieve the goals of learning Indonesian.